A intervenção psicopedagógica na relação escola e família: uma revisão bibliográfica - Luz, Amanda Nataniele De Sousa (Universidade Federal do Tocantins, 2023)
This research aimed to investigate the importance of psychopedagogy as a mediator of the school and family relationship in the context of Special and Inclusive Education (Learning Disorders and Difficulty) and; for specific purposes, researching the relationship between family and school and their influence on the learning process; review the concept of inclusive education and its specific legislation, and what is the role of the family and the school; present the psychopedagogical intervention, its concepts and applications to help improve the relationship between the family and the school for the benefit of the student. Therefore, the methodology used was the Literature Review in the Pedagogy area, through articles already published, where the search was made in “Google Academic” or “Google Scholar”, which is the English term. Thus, considering the way the problem is exposed, the research is qualitative, in Portuguese, with a time filter from 2010 to 2021. Not enough research was found to make a more recent time frame, and with the criteria established, hence the need to add older research that is also interesting and of great relevance to this work.